2021
DOI: 10.3390/ijerph18031038
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future Trends in the Laboratory Diagnosis of Sexually Transmitted Infections

Abstract: Sexually transmitted infections (STIs) continue to exert a considerable public health and social burden globally, particularly for developing countries. Due to the high prevalence of asymptomatic infections and the limitations of symptom-based (syndromic) diagnosis, confirmation of infection using laboratory tools is essential to choose the most appropriate course of treatment and to screen at-risk groups. Numerous laboratory tests and platforms have been developed for gonorrhea, chlamydia, syphilis, trichomon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 118 publications
(142 reference statements)
0
28
0
2
Order By: Relevance
“…According to ISS, the most frequently registered STIs in Italy from 1991 to 2017 were anogenital HPV infection (42.4%), latent syphilis (8.4%), genital herpes (7.3%) and non-chlamydial non-gonococcal bacterial cervicovaginitis (7.1%) [ 4 ]. Regarding asymptomatic STIs cases, previous Italian studies reported high incidence in the female general population as well as in the HIV subgroup [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to ISS, the most frequently registered STIs in Italy from 1991 to 2017 were anogenital HPV infection (42.4%), latent syphilis (8.4%), genital herpes (7.3%) and non-chlamydial non-gonococcal bacterial cervicovaginitis (7.1%) [ 4 ]. Regarding asymptomatic STIs cases, previous Italian studies reported high incidence in the female general population as well as in the HIV subgroup [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we offer our perspectives on the development of POC tests with the goal of facilitating future developments. Our article therefore complements current reviews that put emphasis on either technology development 14 or STIs, [15][16][17][18][19] and together offer a holistic view on bringing NAAT-based STI POCT technologies to patient care.…”
Section: Introductionmentioning
confidence: 78%
“…The symptom-based management of STIs is limited, and current and future trends are the laboratory diagnosis of STIs. Point-of-care testing and microfluidic and high-throughput omics technologies promise to revolutionize the diagnosis of STIs [ 42 ]. Therefore, strategies to screen all HIV-positive individuals for HSV-2, syphilis, MG, and so on would be necessary.…”
Section: Discussionmentioning
confidence: 99%